Race and the income-achievement gap - Ryan Bacic; Angela Zheng (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2023)
We study whether racial disparities in economic opportunity appear at an early age. Using administrative education data linked to tax records, we study the income-achievement gap across different races and find important variation. The income-achievement gap is small for East Asian children while it is close to twice as large for Indigenous children. Sorting by income into schools accounts for a large portion of the variation in the income-achievement gap across all student groups. In addition, our results suggest that the large income-achievement gap for Indigenous students may be rooted in inequality in health outcomes and poor housing conditions. Our findings on income-achievement gaps across race could partially explain the different intergenerational mobility outcomes by race documented by others.
Keywords: I20; I24; J15; 330; test scores; income-achievement gaps; race